1H nuclear magnetic resonance (NMR) metabolomics in rodent plasma: a reproducible framework for preclinical biomarker discovery - Mohd Nawi, Mohd Naeem; Radzi, Ranina; Ali, Azizan; Che Lem, Siti Zubaidah; Zulkapli, Azlina; Lokman, Ezarul Faradianna; Fazliana, Mansor; Narayanan, Sreelakshmi Sankara; Chinna, Karuthan; Md Noh, Mohd Fairulnizal; Mat Daud, Zulfitri Azuan; Karupaiah, Tilakavati (Multidisciplinary Digital Publishing Institute, 2025)
This protocol paper outlines a robust and reproducible framework for a 1H nuclear magnetic resonance (NMR) metabolomics analysis of rodent plasma, designed to facilitate preclinical biomarker discovery. The protocol details optimised steps for plasma collection in a preclinical rodent model, sample preparation, and NMR data acquisition using presaturation Carr–Purcell–Meiboom–Gill (PRESAT-CPMG) pulse sequences, ensuring high-quality spectral data and effective suppression of macromolecule signals. Comprehensive spectral processing and metabolite assignment are described, with guidance on multivariate and univariate statistical analyses to identify metabolic changes and potential biomarkers. The framework emphasises methodological rigour and reproducibility, enabling accurate quantification and interpretation of metabolites relevant to disease mechanisms or therapeutic interventions. By providing a standardised approach, this protocol supports longitudinal and translational studies, bridging findings from rodent models to clinical applications and advancing the reliability of metabolomics-based biomarker discovery in preclinical research.